Akit Tribe Career Aspirations - Ihsandi, Aldi; Eddy Wibowo, Mungin; Sunawan, Sunawan (Universitas Negeri Semarang, 2023)
Researches on career aspirations are often done to university and school students in which they have sufficient career information, but those are rarely done to inland tribe adolescents. Therefore, this research was focused on investigating the underlying career aspirations of the Akit tribe adolescents. It used a qualitative method with a phenomenological approach. For the data, this research involved 13 informants with inclusion criteria. Their data were collected using interviews, observation, and documentation. The collected data were validated using source and method triangulations. Following the triangulation, the analysis was carried out using a Miles and Huberman model which comes up with four stages, namely data collection, data reduction, data presentation, and conclusion drawing and verification. Findings have proved that the fundamental assumptions of career aspirations by the sukit adolescents were finding a stable and secured job, becoming an expert at a particular field, and getting better education. It shows that the sukit adolescents have career aspirations, so there is a need for providing information to help them achieve the desired career.